Nirvana and Timelessness - Smart, Ninian (Journal of Dharma, 1976)
What, after all, is nirvana? It is a cooling off, a quenching of the fire of tanha; but above all it is liberation. It is the iivanmukti and moksa of Buddhist tradition. But with regard to liberation we must always ask: From what and to what? On the latter point, the "to what". the Theravada can be said to be embarrassingly silent, till we grasp the point: to that I shall come a little later. But as to the "from what" there is an embarrassment of riches of description. Consider the whole notion of dukkha, the theory of impermanence, the grand panorama of rebirth, the psychology of Buddhism, and so on. Still all that can be from one angle reduced to a single thought: impermanence. So we have the polarity or dialectic-impermanent existence and (on the other hand) liberation. I believe that the analysis of impermanence is the essentially brilliant contribution of the message of the Buddha.